2012
DOI: 10.1163/15692108-12341234
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Household Access to Formal Credit in the Rural Areas of the Mekong Delta, Vietnam

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 31 publications
5
45
1
2
Order By: Relevance
“…The coefficient on farm capital had a positive and significant relationship with access to microcredit at the 10% level of significance. The result is consistent with Duy et al (2012) who found that a household's capital endowments are very important in the demand for formal credit as well as loan amount. Smallholder farmers are usually resource-poor and have little capital endowment.…”
Section: Determinants Of Access To Microcredit By Rural Householdssupporting
confidence: 91%
See 2 more Smart Citations
“…The coefficient on farm capital had a positive and significant relationship with access to microcredit at the 10% level of significance. The result is consistent with Duy et al (2012) who found that a household's capital endowments are very important in the demand for formal credit as well as loan amount. Smallholder farmers are usually resource-poor and have little capital endowment.…”
Section: Determinants Of Access To Microcredit By Rural Householdssupporting
confidence: 91%
“…Analysis of the factors influencing smallholder farmers' access to microcredit has been carried out by various researchers such as Sebopetji andBelete (2009), Sanusi andAdedeji (2010), Duy et al (2012), Ibrahim and Aliero (2012), Chauke et al (2013) and Nouman et al (2013). Very few researchers such as Duy et al (2012) have analysed access to credit taking into account the possible presence of selectivity bias arising from non-random sampling of borrowers and non-borrowers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…VBSP is considered as a simple microfinance bank based on the scale of operation and the number of poor clients by the government of Vietnam's support policies [37]. The numbers of poor people able to access microfinance programs has increased significantly over the last two decades [36,39]. Microfinance operations have been contributing to job creation for the poor and this can help diversify the sources of income in the household.…”
Section: Lessons From Microfinance In Vietnammentioning
confidence: 99%
“…Adicionalmente, Nguyen (2007) y Duy et al (2012) estudian los determinantes del crédito formal en la zona rural de Vietnam; en general encuentran que dentro de los factores más importantes están el tamaño del hogar, el trabajo del jefe del hogar en el sector agrícola o por cuenta propia, estado civil (casado), la distancia el mercado, la dotación de capital de los hogares y la región donde viven.…”
Section: Revisión De Literaturaunclassified